Metode Relaksasi Untuk Menurunkan Stres dan Keluhan Tukak Lambung pada Penderita Tukak Lambung Kronis - Tri Subekti; Muhana Sofiati Utami (Faculty of Psychology, Universitas Gadjah Mada, 2011)
Individual disability to manage stress results the body become susceptible to diseases so that some physical disorders like gastritis enable to see. Gastritis represent one of psychosomatic disorders, aphysiological disorder caused by a major psychological factor, stress as a common. This research is aimed to test the relaxation method that is used to lessen stress and the sigh of gastritis pain for thepatients of chronic gastritis. The research applies the single case experimental design. Subjects of the research are three women who get treatment of Imagery Relaxation Therapy and Muscle RelaxationTherapy for three times. Then, they are monitored by self monitoring for 3 weeks. The instruments used in this experiment are Scale of Stress compiled by Prawitasari (1989), and Sigh of GastritisPain Scale adapted from Sigh of Physical Gastritis Scale compiled by Sutrisno (1998). The data analysed in manual through some visual inspection to compare the level of stress and sigh of gastritispain of each subject among the baseline, treatment and follow-up. Results showed that there is decreases of stress and sigh of gastritis pain of the subjects. They also showed clinical significancy.